2020
DOI: 10.1186/s12977-020-00528-y
|View full text |Cite
|
Sign up to set email alerts
|

M-Sec facilitates intercellular transmission of HIV-1 through multiple mechanisms

Abstract: Background HIV-1 promotes the formation of tunneling nanotubes (TNTs) that connect distant cells, aiding cell-to-cell viral transmission between macrophages. Our recent study suggests that the cellular protein M-Sec plays a role in these processes. However, the timing, mechanism, and to what extent M-Sec contributes to HIV-1 transmission is not fully understood, and the lack of a cell line model that mimics macrophages has hindered in-depth analysis. Results We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…The components of the exocyst complex interact with several small GTPases (Rho1, Rho3, Cdc42, and RalA) to promote actin cytoskeletal remodeling, which is closely related to the function of the exocyst complex (69,71,72). The exocyst complex also participates in the formation of TNTs, and this process is controlled by M-Sec, a protein that has been proven to control the formation of TNTs (73,74). M-Sec can promote the assembly of the exocyst complex and interact with it, as well as with RalA (or Cdc42), leading to actin cytoskeleton remodeling, which is the key step of TNT formation (75).…”
Section: Methods Of Transcellular Transfer Of Mitochondria Transfer Via Tntsmentioning
confidence: 99%
“…The components of the exocyst complex interact with several small GTPases (Rho1, Rho3, Cdc42, and RalA) to promote actin cytoskeletal remodeling, which is closely related to the function of the exocyst complex (69,71,72). The exocyst complex also participates in the formation of TNTs, and this process is controlled by M-Sec, a protein that has been proven to control the formation of TNTs (73,74). M-Sec can promote the assembly of the exocyst complex and interact with it, as well as with RalA (or Cdc42), leading to actin cytoskeleton remodeling, which is the key step of TNT formation (75).…”
Section: Methods Of Transcellular Transfer Of Mitochondria Transfer Via Tntsmentioning
confidence: 99%
“…Another potential role for TNTs in cell-to-cell fusion concerns HIV-1 infection of macrophages [ 111 , 197 , 206 , 207 ], which are prone to form MGCs (see “ Introduction ”). In this context, we revealed a correlation between the formation of TNTs at the early stages of HIV-1 infection of human macrophages and the extent of the fusion later on [ 57 , 111 , 195 , 197 , 208 ].…”
Section: Tunneling Nanotubes and Myeloid Cell Fusionmentioning
confidence: 99%
“…In this context, we revealed a correlation between the formation of TNTs at the early stages of HIV-1 infection of human macrophages and the extent of the fusion later on [ 57 , 111 , 195 , 197 , 208 ]. In terms of molecular actors, M-Sec mediates rapid and efficient cell-to-cell transmission of HIV-1 at an early phase of infection by enhancing both cell motility, TNT formation, and number of nuclei per infected macrophages [ 207 ]. Finally, Cx43 localizes at the tip of close-ended TNTs formed between HIV-infected macrophages, suggesting that stabilization of long-range gap junction-dependent communication could favor HIV-1 transfer [ 206 ].…”
Section: Tunneling Nanotubes and Myeloid Cell Fusionmentioning
confidence: 99%
“…We recently demonstrated that M-Sec promotes cell-to-cell infection of HIV-1 [ 8 , 9 ]. Small molecule compound that inhibits M-Sec-induced membrane protrusions reduced HIV-1 production in monocyte-derived macrophages [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Small molecule compound that inhibits M-Sec-induced membrane protrusions reduced HIV-1 production in monocyte-derived macrophages [ 8 ]. Moreover, the knockdown of M-Sec retarded HIV-1 production in U87 glioma cells [ 9 ], a widely-used HIV-1 target cell line. As M-Sec inhibition or knockdown reduces membrane protrusions and cell migration in these cells [ 8 , 9 ], M-Sec appears to contribute to the initial phase of HIV-1 transmission by enhancing membrane protrusions and cell migration.…”
Section: Introductionmentioning
confidence: 99%